Endoscopic full-thickness resection of colonic submucosal tumors originating from the muscularis propria: an evolving therapeutic strategy - Xu, Meidong; Wang, Xiao-Yun; Zhou, Ping-Hong; Li, Quan-Lin; Zhang, Yiqun; Zhong, Yunshi; Chen, Weifeng; Ma, Lili; Ishaq, S.; Qin, Wenzheng; Hu, Jianwei; Yao, Liqing (Endoscopy, 2013)
Endoscopic resection of colonic submucosal tumors (SMTs) is challenging and carries a high risk of perforation. In this prospective pilot study we aimed to evaluate the feasibility, safety, and efficacy of endoscopic full-thickness resection of colonic SMTs. The study enrolled 19 consecutive patients with colonic SMTs 3 cm in size or smaller. In 18 of the 19 patients full-thickness resection was carried out endoscopically with the entire tumor capsule intact. In 16 of these18 patients, full-thickness resection was carried out and the colonic wall defect closed all endoscopically; in the other 2 patients, laparoscopic closure was needed. Two cases of local peritonitis were managed with conservative treatment. No deaths occurred within 30 days, and no recurrence was detected after a median of 18 months’ follow-up. Endoscopic full-thickness resection is a novel method enabling resection of colonic SMTs. The colonic wall mucosal defect can be closed endoscopically in the majority of cases. It appears to be a safe and effective endoscopic technique for managing these tumors, which traditionally are managed by colonic resection.